Sectoral Interconnectedness: insights from five sectors in ‘smart’ urban planning (Energy, Transport, Waste Management, Buildings, and Cities) - Vincent Onyango; Maryam Forghaniallahabadi; Sandra Costa Santos; Paola Gazzola (European Scientific Journal, ESJ, 2025)
‘Smart’ urban planning has become essential for addressing contemporary urban challenges, with sectoral interconnectedness at its core for achieving sustainable, efficient, and resilient cities. Yet it remains unknown to what extent the elements of smart are interlinked across the sectors. Therefore, this paper examines the degree of interconnectedness across five smart sectors: Energy, Transport, Waste management, Buildings, and Smart cities, covering site to city-wide scale. A mixed-method approach was employed, combining qualitative thematic coding and quantitative correlation analysis using NVivo's suite of cluster analysis tools. Strong interconnectedness was identified between the Energy and Transport sectors, driven by digital transformation and data-driven decision-making. In contrast, weak interconnectedness was observed between transformative cross-sectoral (CS) goals such as climate adaptation and sustainability. Smart Cities was the most interconnected sector, acting as a central platform where CS goals like sustainability, digital transformation, and real-time data utilization converge. Nevertheless, sectoral silos and inconsistent interoperability threaten the realization of holistic smart urban outcomes. This highlights the urgent need for cohesive frameworks that systematically align CS goals across sectors, ensuring that technological innovations contribute meaningfully to long-term environmental and social objectives. The paper’s insights can help policymakers and practitioners strengthen cross-sector collaboration, optimize urban systems, and promote integrated, adaptive, and sustainable smart urban planning.